Analisis Pendapatan Petani Jagung yang Ditinjau dari Modal dan Harga Jual: Studi pada Petani Jagung di Desa Tudi Kecamatan Monano - Fitriana Atima; Hartati Tuli; Ronal S.Badu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In Indonesia, corn is a food ingredient that can contribute to the development of the agricultural sector. Development of the agricultural sector is synonymous with efforts to increase community income and welfare. There are various factors that can influence farming income such as capital, selling price, production, land area, and labor. The aim of this research is to determine the income of corn farmers in terms of capital and selling price. This research uses a descriptive qualitative method using primary data obtained through observation, interviews and documentation. The results of this research show that the average level of income of farmers in terms of selling prices produces income for one harvest which is quite high because the average selling price received during the last harvest by farmers was IDR 4,800/kg. This is also a high selling price. will produce a large income, while the farmer's income level in terms of capital to produce one harvest is quite low due to the varying differences in capital expenditure. This can occur because the purchase price of tools, materials and wage costs incurred by each informant is different, this causes large the small amount of capital spent will affect the level of income generated.